Implementation of Health Insurance System in Independent Practice Midwives (Bpm) in the Framework of Maternal and Child Health According to Law Number 40 Year 2004 (Study in Surabaya City) - Diana Rahima; Mas Anienda Tien Fitria (Universitas Merdeka Madiun, 2024)
Abstract Introduction to the Problem: Health is a basic right guaranteed by the Indonesian constitution. The government, through BPJS Kesehatan, seeks to provide access to health services for all, including mothers and children. However, Independent Practitioner Midwives (BPM) often face obstacles in cooperation with BPJS. Purpose/Study Objectives: This study examines the implementation and constraints of the BPM health insurance system according to Law No. 40 of 2004. Design/Methodology/Approach: Primary data was obtained through observation and interviews with independent practicing midwives (BPM) in Surabaya. Secondary data came from legislation and legal literature. The analysis is done qualitatively by integrating empirical data and literature study to get a systematic conclusion. Findings: The health insurance system in independent midwives (BPM) provides access to maternal and child health in accordance with Law No. 40 Year 2004. BPMs are obliged to cooperate with BPJS Health to ensure affordable and quality health services. However, BPMs often face administrative and technical obstacles in establishing cooperation with BPJS, affecting the effectiveness of services.The implementation of the health insurance system in Independent Practitioner Midwives (BPM) in accordance with Law No. 40/2004 has improved access to maternal and child health in Indonesia. BPMs that cooperate with BPJS Health help reduce maternal and infant mortality rates. However, administrative, technical and financial constraints remain. Solutions include simplifying administration, improving facilities, and improving the claims payment system. Paper Type: Research Article